Soluble Two‐Dimensional Covalent Organometallic Polymers by (Arene)Ruthenium‐Sulfur Chemistry. Issue 46 (26th July 2017) - Coraux, Johann; Hourani, Wael; Müller, Valentin L.; Lamare, Simon; Kamaruddin, Danial Aiman; Magaud, Laurence; Bendiab, Nedjma; Den Hertog, Martien; Leynaud, Olivier; Palmino, Frank; Salut, Roland; Chérioux, Frédéric
Abstract: A class of two‐dimensional (2D) covalent organometallic polymers, with nanometer‐scale crosslinking, was obtained by arene(ruthenium) sulfur chemistry. Their ambivalent nature, with positively charged crosslinks and lypophylic branches is the key to the often sought‐for and usually hard‐to‐achieve solubility of 2D polymers in various kinds of solvents. Solubility is here controlled by the planarity of the polymer, which in turn controls Coulomb interactions between the polymer layers. High planarity is achieved for high symmetry crosslinks and short, rigid branches. Owing to their solubility, the polymers are easily processable, and can be handled as powder, deposited on surfaces by mere spin‐coating, or suspended across membranes by drop‐casting. The novel 2D materials are potential candidates as flexible membranes for catalysis, cancer therapy, and electronics. Abstract : Powder up : A two‐dimensional material, consisting of (arene)ruthenium‐sulfur crosslinks and polyphenylic branches, was synthesized in solution. Its ambivalent nature provides affinity with a variety of solvents, while its flatness and rigidity minimize interlayer interactions. As a result, the polymer is easily soluble and processable in a versatile way.